2001
DOI: 10.1073/pnas.151131498
|View full text |Cite
|
Sign up to set email alerts
|

Energetic asymmetry among hydrogen bonds in MHC class II⋅peptide complexes

Abstract: Comparison of crystallized MHC class II⅐peptide complexes has revealed that, in addition to pocket interactions involving the peptide side chains, peptide binding to MHC class II molecules is characterized by a series of hydrogen bonds between genetically conserved amino acid residues in the class II molecule and the main chain of the peptide. Many class II⅐peptide structures have two sets of symmetrical hydrogen bonds at the opposite ends of the class II antigen-binding groove (␤-His-81, ␤-Asn-82 vs. ␣-His-68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
47
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 33 publications
10
47
0
Order By: Relevance
“…In the case of a 420-residue protein, I-E k -Hb, the pI value in the denatured state is estimated to be 4.8 from the amino acid composition, and that in the native state is estimated to be 5.0 by the isoelectric focusing experiments (data not shown). Amino acid residues such as Asp and His, with charges that are affected at the pH region analyzed in this study, are thought to be involved in the structural and functional characters of MHC class II molecules (16,30,31). Therefore, the present thermodynamic results obtained in phosphate buffer, which has lower enthalpy change for the deprotonation, could be the comparable data to analyze the effects of pH on the stability difference of I-E k -Hb.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the case of a 420-residue protein, I-E k -Hb, the pI value in the denatured state is estimated to be 4.8 from the amino acid composition, and that in the native state is estimated to be 5.0 by the isoelectric focusing experiments (data not shown). Amino acid residues such as Asp and His, with charges that are affected at the pH region analyzed in this study, are thought to be involved in the structural and functional characters of MHC class II molecules (16,30,31). Therefore, the present thermodynamic results obtained in phosphate buffer, which has lower enthalpy change for the deprotonation, could be the comparable data to analyze the effects of pH on the stability difference of I-E k -Hb.…”
Section: Discussionmentioning
confidence: 73%
“…The protonation of these carboxylate groups at low pH, together with other residues such as His 81 of the ␤ subunit, facilitates the flexibility and the conformational change of the MHC class II molecule from the closed to the open form (30). In addition, the recent mutational analyses of HLA-DR, the human homologue of I-E k , have shown that His 33 of the ␣ subunit has the role of a pH-sensitive switch at low pH, which can regulate the conformational transition and the peptide exchange (31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has demonstrated that in I-A d class II molecules, these different sets of hydrogen bonds contribute disproportionately to peptide-MHC stability. The loss of hydrogen bonds near the amino terminus of the bound peptide, as previously demonstrated, resulted in substantial acceleration in peptide dissociation, whereas the loss of hydrogen bonds near the peptide's carboxyl terminus were shown to have significantly less effect, indicating that they contribute less to complex stability (32). We have not yet explored the relative importance of individual hydrogen bonds in human class II molecules, although the hydrogen bonding network was first noted in these crystal structures (9,33).…”
Section: Discussionmentioning
confidence: 85%
“…This first rearrangement would indeed trigger the involvement of the adjacent, partially disordered, ␣1/␤1 helical regions and it would facilitate the formation of the other pocket/side chain interactions. At first, the nucleus would be stabilized by the interactions in the P(Ϫ1) to P2 region, where the H-bonds between His␤ (81) and Asn␤ (82), as well as the residues from ␣ (51) to ␣ (53), and the bound peptide, have been recognized as critical for the complex stability (31)(32)(33). Then, the onrush of cooperative interactions would operate: 1) inducing the folding of the helices; 2) inducing the other hydrophobic pocket interactions; 3) stabilizing both types of binding energy; 4) inducing the folding of the peptide into a polyproline type II conformation.…”
Section: Discussionmentioning
confidence: 99%